The role of participation and communication for energy efficient refurbishment - Antje Bretzmann; Thomas Bäumer; Stephanie Huber (Economic and Environmental Studies (E&ES), 2017)
The effort of changing energy production and supply in Germany has not only led to innovative power supply concepts and large grid expansions, but also to ambitious goals for low and zero carbon (LZC) technologies in residential buildings. The present research project has a specific focus within this context: apartment buildings with a large number of flat owners. Prior to any major refurbishment, whether standard or energy efficient, the owner community needs to make decisions based on a majority consensus. Considering the financial strain and the wide-ranging impact for future living, these majority decisions have not always been easy to make. Effectively, they have been a serious barrier for the implementation of energy efficient refurbishment in large apartment houses with a heterogeneous ownership structure. Therefore, both a participation framework and an adequate communication concept for this particular stakeholder group are needed. Approaches from various fields, e.g. acceptance research, psychology, Design Thinking, and communication studies can be applied in order to integrate all owners into the planning process and find energy efficient solutions that most owners can agree on. This paper introduces a participation and communication framework for energy efficient refurbishment with defined participation stages and communication formats. Derived from this framework and preceding studies, ten essential communication recommendations are formulated that ensure the success of the planning process. Apart from classical communication instruments, one focus of the framework is on the implementation of applicable online activities. Furthermore, based on the Design Thinking idea, the needs and requirements of the target group should be identified at an early stage of the planning process. Consequently, these demands can be incorporated into the entire process by presenting customized offers. The paper concludes with a discussion of the presented framework and an outlook for innovative opportunities of participation in order to enhance refurbishment rates in large apartment houses with multiple owners.
Keywords: Q; O; 330; energy efficient refurbishment; sustainability; communication; participation